Conjunctive Use of Water Resources in Sustainable Development of Agriculture in Terai Nepal - Bhattarai, Debi Prasad; Shakya, Narendra Man (Journal of the Institute of Engineering, 2019)
The need of conjunctive use of surface and ground water resources in agricultural sector arises due to the continuous increase in population and its growing demand for the production of food and fiber globally. United Nations Sustainable Development Goal 2 also targets to double the agricultural productivity to feed the growing population and ensure sustainable food production systems by 2030. The conjunctive uses allow the utilization of ground water and surface water simultaneously as per the demand and supply requirement of available water resources. This paper presents an overview of the conjunctive use practices in the different parts of the world in general and specific issues for conjunctive use of irrigation for sustainable agriculture in the Terai region of Nepal. It covers a synopsis of literatures available regarding the conjunctive use of irrigation system in different irrigation command area of Nepal and unveils some research issues that need to be addressed. The review also covers an overview of different computer based models developed for the management of conjunctive water use for irrigated agriculture. Based on the review conclusions are drawn which could be helpful for further research and for the management of conjunctive irrigation system in the Terai region of Nepal.